Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The multifunctional fish gill - Steve F. Perry; Bernd Pelster (Journal of Comparative Physiology B, 2024)

Effects of serta and sertb knockout on aggression in zebrafish (Danio rerio) - Michael Tea; Yihang Kevin Pan; Joshua G. R. Lister; Steve F. Perry; Kathleen M. Gilmour (Journal of Comparative Physiology A, 2024)

Physiology and aquaculture: A review of ion and acid‐base regulation by the gills of fishes - Alex M. Zimmer; Steve F. Perry (Fish and Fisheries, 2022)
Fish aquaculture facilities strive to maintain abiotic conditions that optimise somatic growth. Two physiological systems that are critically linked to environmental abiotic factors are ion and acid‐base regulation. Given the detrimental effects of ionic and acid‐base imbalances coupled with the potential energetic costs of ion and acid‐base regulation, it is important to understand how changes in abiotic variables such as salinity, temperature and pH alter ionoregulatory and acid‐base physiology. The gill is the predominant site of ion and acid‐base regulation, two linked processes that are vital to the health of fishes. Most species maintain ion levels in the blood plasma within a narrow range, independent of external ion concentrations. In freshwater (FW), fishes must actively take up ions from their dilute environment to counteract passive ion losses, while in seawater (SW), ion excretion serves to counteract passive salt gain. Ion uptake (FW) and excretion (SW) are coordinated by different subtypes of ion‐transporting cells (ionocytes) expressed in the gill epithelium. In this review, we discuss the function of FW and SW ionocytes in the movement of ions across the gill epithelium and address other features of the gill that are integral to ionoregulation. We also discuss the mechanisms of acid‐base regulation by the gill, which is intimately related to ion regulation because it is coordinated by Na + ‐ and Cl − ‐linked fluxes of acid (H + ) and base () equivalents. These fundamental physiological principles are integral in understanding how fishes in aquaculture respond to relevant disturbances that may occur under culture conditions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Does hypoxia-inducible factor 1α play a role in regulating cutaneous oxygen flux in larval zebrafish (Danio rerio)? - Julian J. Parker; Steve F. Perry (Journal of Comparative Physiology B, 2021)

Air breathing and aquatic gas exchange during hypoxia in armoured catfish - Graham R. Scott; Victoria Matey; Julie-Anne Mendoza; Kathleen M. Gilmour; Steve F. Perry; Vera M. F. Almeida-Val; Adalberto L. Val (Journal of Comparative Physiology B, 2017)

Hydrogen sulfide inhibits Na+ uptake in larval zebrafish, Danio rerio - Yusuke Kumai; Cosima S. Porteus; Raymond W. M. Kwong; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

A role for transcription factor glial cell missing 2 in Ca2+ homeostasis in zebrafish, Danio rerio - Yusuke Kumai; Raymond W. M. Kwong; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

Extracellular H+ induces Ca2+ signals in respiratory chemoreceptors of zebrafish - Sara J. Abdallah; Michael G. Jonz; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

Linking physiological and cellular responses to thermal stress: β-adrenergic blockade reduces the heat shock response in fish - Nicole M. Templeman; Sacha LeBlanc; Steve F. Perry; Suzanne Currie (Journal of Comparative Physiology B, 2014)

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

Evidence for a role of tight junctions in regulating sodium permeability in zebrafish (Danio rerio) acclimated to ion-poor water - Raymond W. M. Kwong; Yusuke Kumai; Steve F. Perry (Journal of Comparative Physiology B, 2013)

The interactive effects of exercise and gill remodeling in goldfish (Carassius auratus) - Steve F. Perry; Carmen Fletcher; Shawn Bailey; Jaimee Ting; Julia Bradshaw; Velislava Tzaneva; Kathleen M. Gilmour (Journal of Comparative Physiology B, 2012)

The effects of gill remodeling on transepithelial sodium fluxes and the distribution of presumptive sodium-transporting ionocytes in goldfish (Carassius auratus) - Julia C. Bradshaw; Yusuke Kumai; Steve F. Perry (Journal of Comparative Physiology B, 2012)

Interactive effects of development and hypoxia on catecholamine synthesis and cardiac function in zebrafish (Danio rerio) - Shelby L. Steele; Marc Ekker; Steve F. Perry (Journal of Comparative Physiology B, 2011)

Acid–base regulation in the plainfin midshipman (Porichthys notatus): an aglomerular marine teleost - Steve F. Perry; Marvin H. Braun; Janet Genz; Branka Vulesevic; Josi Taylor; Martin Grosell; Kathleen M. Gilmour (Journal of Comparative Physiology B, 2010)